Carbon dioxide removal in emulsion liquid membrane containing 2-amino-2-methyl-1-propanol /monoethanolamine - Suahadah, S. N. (2015)
Absorption using aqueous alkanolamine is commonly used in industry to remove the carbon dioxide. However it has several weaknesses such as corrosion problem and low absorption rate. Emulsion liquid membrane is introduced as an alternatives method for CO2 absorption because it can reduce the corrosion problem and the formation water droplets creates large interfacial area for absorption to occur. 2-amino-2-methyl-1-propanol (AMP) and monoethanolamine (MEA) present in the aqueous phase in the form of aqueous droplets, surrounded by the organic solution to form water in oil (w/o) emulsion. In this study, effects of amines ratios and amine quantities, and emulsification time and speed on the ELM stability and CO2 absorption were investigated. The ELM was prepared by homogenizing the aqueous and the organic phases. AMP and MEA were added into sodium hydroxide (NaOH) solution to form aqueous solution, and kerosene and Span-80 were mixed to form the organic solution. The absorption study was carried out in rotating disc contactor (RDC) column. A mixture of 12 v% MEA, 4 v% AMP in 100 ml aqueous solution and 8 v% Span-80 in 100 ml organic phase has high stability and can remove 60% of CO2. The stability of the emulsion remained high even after the absorption. This study proved that ELM has the potential to remove CO2 by using only small amount of amines.